The effect of clomiphene citrate and human chorionic gonadotropin on the expression of CatSper1, CatSper2, LHCGR, and SF1 genes, as well as the structural changes in testicular tissue of adult rats. Issue 6 (30th April 2019) - Ameli, Mojtaba; Moghimian, Maryam; Saeb, Farzaneh; Bashtani, Elham; Shokoohi, Majid; Salimnejad, Ramin; Abtahi, Hossein
Abstract: The purpose of this study was to investigate the effect of clomiphene citrate and human chorionic gonadotropin (HCG) on the structural changes, as well as the evaluation of the expression of cation channel sperm‐associated protein 1 (CatSper1), cation channel sperm‐associated protein 2 (CatSper2), luteinizing hormone/choriogonadotropin receptor (LHCGR), and steroidogenic factor 1 (SF1) genes in testicular tissue of rats. All rats divided into five groups as follows; G1 as the control group that received normal saline, G2 received olive oil, G3 received 100 IU/kg HCG, G4 received 5 mg/kg clomiphene citrate, and G5 received 5 mg/kg clomiphene citrate and 100 IU/kg HCG. At the end of the experiment period, Day 56, blood samples were taken and the serum was isolated. Then, histomorphometric analysis, hormonal assess, and real‐time polymerase chain reaction to measure the expression of CatSper1, CatSper2, LHCGR, and SF1 genes were performed. The results showed that the concentrations of testosterone, follicle‐stimulating hormone, and luteinizing hormone were decreased in the G4 group, whereas these parameters were increased in the G3 group. A comparison of the sperm quality indicated a significant reduction in the quality of sperm cells in the G4 group compared with other groups. The quality of sperm was significantly enhanced in the G3 and G5 groups in comparison with the G1 group. Also, our findings demonstrated that the expression of CatSper1, CatSper2, LHCGR, and SF1 genes were significantly elevated in the G3 group when compared with other experimental groups. According to the obtained results, it seems that clomiphene citrate reduces the process of spermatogenesis and the detrimental impacts of this compound would be neutralized by the administration of HCG. Abstract : Administration of human chorionic gonadotropin (HCG) can enhance the expression of cation channel sperm‐associated protein 1 (CatSper1), cation channel sperm‐associated protein 2 (CatSper2), steroidogenic factor 1 (SF1), and luteinizing hormone/choriogonadotropin receptor (LHCGR) genes. Administration of clomiphene citrate decreased the expression of CatSper1, CatSper2, SF1, and LHCGR genes. Administration of HCG with clomiphene citrate together can protect the negative effect of clomiphene citrate on testis tissue and sperm quality.